2013
DOI: 10.1128/iai.00973-13
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Interaction with Neutrophils and Macrophages In Vitro and in SCID Mice following Aerosol Infection

Abstract: Coxiella burnetii is an obligate intracellular bacterium that causes acute and chronic Q fever in humans. Human Q fever is mainly transmitted by aerosol infection. However, there is a fundamental gap in the knowledge regarding the mechanisms of pulmonary immunity against C. burnetii infection. This study focused on understanding the interaction between C. burnetii and innate immune cells in vitro and in vivo. Both virulent C. burnetii Nine Mile phase I (NMI) and avirulent Nine Mile phase II (NMII) were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…It has been shown, however, that primary human alveolar macrophages produce mature IL-1␤ in response to NMII but not phase I C. burnetii, suggesting that human and mouse inflammasome sensors or various cell types differ in their responses to NMII infection (54). The finding that NMII does not induce inflammasome activation in mouse cells may provide some insight into the observation that neutrophil recruitment is delayed in mice infected with phase I or phase II C. burnetii until 1 week postinfection (118), as inflammasome-derived IL-1 is a critical regulator of neutrophil recruitment during other bacterial infections, such as pulmonary L. pneumophila infection (68,(90)(91)(92). Further studies are warranted to determine the additional mechanisms by which C. burnetii evades inflammasome activation in mouse macrophages.…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown, however, that primary human alveolar macrophages produce mature IL-1␤ in response to NMII but not phase I C. burnetii, suggesting that human and mouse inflammasome sensors or various cell types differ in their responses to NMII infection (54). The finding that NMII does not induce inflammasome activation in mouse cells may provide some insight into the observation that neutrophil recruitment is delayed in mice infected with phase I or phase II C. burnetii until 1 week postinfection (118), as inflammasome-derived IL-1 is a critical regulator of neutrophil recruitment during other bacterial infections, such as pulmonary L. pneumophila infection (68,(90)(91)(92). Further studies are warranted to determine the additional mechanisms by which C. burnetii evades inflammasome activation in mouse macrophages.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study from our lab found that neutrophils infected with C. burnetii were taken up by macrophages and the bacteria were able to replicate within these macrophages (4). This suggests that neutrophils may not be able to kill C. burnetii directly.…”
Section: Discussionmentioning
confidence: 96%
“…However, a previous study from our lab found that following C. burnetii aerosol infection, neutrophils are not present in the airways until 7 days p.i. (4). The mechanism of this delay is unknown.…”
mentioning
confidence: 99%
“…Studies have shown how bacteria could use neutrophils as an evasive strategy to infect macrophages. 9 The C. burnetii strain that circulates in Spain represents a low risk for Q fever transmission in zoonotic terms. 5,20,23 However, further studies designed to examine the cellular response are needed to clarify the pathogenesis of coxiellosis during acute infection in cattle.…”
Section: Discussionmentioning
confidence: 99%